Effects of an educational Campaign about beans on a group of women. - Dumani, Marcela; Páez, Paola (Agronomía Mesoamericana, 2004)
The effects of an educational Campaign about beans on a group of middle-class mothers with school children who were the target group of this study, are presented in this article. The particular characteristic of this group of women was that their children had also been exposed to the Campaign. The students were the “interactive group”, because their close contact with their mothers, allowed them to act as a communication channel to reinforce the messages addressed to them. The effects are evaluated as knowledge, attitudes, and practices of the mothers with regards to beans, comparing findings with “success indicators” proposed for the Campaign. With the data obtained in the initial assessment it was also possible to make quantitative comparisons of some of the practices. Results revealed that the Campaign had positive effects on women. An important increase in bean consumption by families, a positive attitude about beans, and improvements in their preparation, consumption, and preservation were observed after the Campaign.